(untitled) (Hoboken, 2005)
Maximizing the use of our visible surface supplies in light of their greatest need in agriculture presents an enormous challenge throughout the world. New techniques in agricultural applications to preserve resources and increase yields are featured. Dams, lakes, and hydraulic features of surface water systems are amply covered, along with the importance of storm water management to growing communities.
Keywords: Water,Water quality,Water resources development; Supply